Veno-active drugs for chronic venous disease: A randomized, double-blind, placebo-controlled parallel-design trial. (August 2014) - Belczak, Sergio Q; Sincos, Igor R; Campos, Walter; Beserra, Julio; Nering, Gilberto; Aun, Ricardo
Introduction: Our current understanding of the pathophysiology of chronic venous disease (CVD) suggests that veno-active drugs (VAD) can provide effective symptom relief. Few studies have conducted head-to-head comparisons of VAD and placebo while also assessing objective measures (such as water plethysmography findings and tibiotarsal joint range of motion) and patient-reported quality of life outcomes. Objectives: To compare the effects of different VAD on limb volume reduction, tibiotarsal range of motion, and quality of life. Methods: 136 patients with CVD (CEAP grades 2–5) were randomly allocated into four groups to receive micronized diosmin + hesperidin, aminaphthone, coumarin + troxerutin, or placebo (starch). Patients were administered a questionnaire consisting of a quality of life (QoL) measure designed specifically for persons with CVD, and underwent tibiotarsal joint angle measurement and water plethysmography of the lower extremity before and 30 days after pharmacological intervention. Assessors were blind to the treatment groups. Results: Nine patients dropped out of the trial. Data collected from the 127 remaining patients was considered for statistical analysis. There were no differences in tibiotarsal joint range of motion. Volume reductions ≥100 mL were more frequent in the diosmin + hesperidin group than in any other group. QoL scores were best in the aminaphthone group, and between-group differences were found on individual analysis of questionnaire items. Conclusions: Use of VAD was associated with significant improvements in QoL as compared with placebo. VAD may be effective for providing symptom relief in patients with CVD.